Manipulating task constraints shapes emergence of herding tendencies in team games performance - Yi Hao Tan, T.; Jia Yi, C.; Duarte, R.; Davids, K. (International Journal of Sports Science & Coaching, 2017)
The herding phenomenon is observed in nature and has been perceived to be less desirable use of space in impacting overall team play performance. The effective manipulating of rules and task constraints might be able to alter herding tendencies in sport performance. The aim of this study was to determine the impact of altering task constraints on herding tendencies, measured with the use of cluster phase analysis, which has also been used to analyse the synchrony exhibited by performers in invasion games such as professional association football matches. In this study, tracking positional data of individual players in a simulated pass and catch game was undertaken, with no specific verbal instructions provided to participants on how and where to move so that emergent behavioural tendencies could be observed. Data revealed how task constraint manipulations impacted on herding tendencies. Manipulation of task constraints revealed higher levels of clustering tendencies in the herding condition compared to the non-herding condition. Within the herding condition, between-team synchrony was also strong, especially in the longitudinal direction. Ball possession also seemed to have some impact on within-team synchrony. Findings provided preliminary evidence on how manipulating task constraints can be effective in altering herding tendencies in team games. ABSTRACT FROM AUTHOR